2020
DOI: 10.1186/s12877-019-1409-3
|View full text |Cite
|
Sign up to set email alerts
|

Aging-simulation experience: impact on health professionals’ social representations

Abstract: Background: Health professionals working with older persons are not sufficiently aware of the sensory and functional difficulties experienced by older patients. Innovative educational activities, such as the aging-simulation experience, can facilitate this awareness. This study describes the effects of an aging-simulation experience on health professionals' representations towards age-related limitations. Methods: 306 health professionals, enrolled in university training in geriatrics/gerontology in the 2015-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…A sensory activity, like playing a completely dependent blind person while wearing an age simulation suit, allows students to put themselves in the shoes of older patients [ 4 , 41 ]. In this way, they can develop more empathetic attitudes and their sensitivity to the feelings of others increases [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A sensory activity, like playing a completely dependent blind person while wearing an age simulation suit, allows students to put themselves in the shoes of older patients [ 4 , 41 ]. In this way, they can develop more empathetic attitudes and their sensitivity to the feelings of others increases [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aged simulation suits have been used effectively with health professionals to increase understanding of age‐related changes, 7 and to improve skills, knowledge and attitudes 15 …”
Section: Introductionmentioning
confidence: 99%
“…A new aged simulation training suit has been developed by the Broken Hill Rural Clinical School, at the University of Sydney, over a period of ten years. The aged simulation training suit (ASTS) is an experiential learning tool that enables health‐care professionals, including PCAs, to gain an understanding of the level of social isolation, sensory loss and functional difficulties experienced by the older person in their daily life 7,17 …”
Section: Introductionmentioning
confidence: 99%
“…Aging simulations have been conducted with medical, nursing, and pharmacy students in different countries [ 7 – 10 ]. Although reviews have found mixed results of teaching interventions in geriatric medicine in general [ 4 , 11 ] and educational role playing games in particular [ 12 ], single studies report significant increases in positive attitudes toward (caring for) older patients [ 3 , 6 , 10 ] and awareness of age-related difficulties [ 1 , 13 ].…”
Section: Introductionmentioning
confidence: 99%